Efectos de la masticación unilateral en el sistema estomatognático y posibles factores predisponentes en niños escolares de Medellín - Mejía-Vanegas, Giovanni Alfredo; Godin-Rubio, Ana Milena; Perez-Osorio, Luis Javier (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Unilateral mastication is understood as an alteration of the physiologic functioning of the stomatognatic system, which creates Unbalanced forces, concentrating those in onside, the working side, leading to changes in dental, muscular and skeletal systems. It affects mostly young people whose bodie’s structures are hi& adaptative. The purpose of this study is to establish if there are differences in the components of the stomatognatic system in subjects with unilateral mastication, between. The working side with is usualy favorect and the les,s functional side. It also pretends to describe those differences and to establish some factors thar could influence the choosing of the favorite side formastication. We studied 39 subjects, all of them with unilateral mastication. Thirthy-five variables were analized II in relation to dental and medical antecedents, 8 to clinical examination and 11 to the evaluation of the plaster casts. In reference to the relationship between unilateral mastication and the possible factors which could influence the choosing of a side for mastication we found that the habit of bitting-pencils and other objects was the only one with showed statistical significance. In reference to the relationship between the type of unilateral mastication and the possible modifications in the structures of the stomatognathic system, the difference in the form of the head of the condyle and the anteroposterior right and left lenght of the inferior arch, showed statistical significance, there erist a tendency of non-coincidence between R.C.P. and H.O. in subjects with unilateral mastication. The other variables didn’t show statistical significance.